Ultrasonographic monitoring of abdominal wound healing in ewes - Mallick, Sourav; Hasan, Moinul; Juyena, Nasrin Sultana; Biswas, Dhriti Sundhar; Shoriotullah, Mohammad; Alam, Md Rafiqul (Journal of Advanced Veterinary and Animal Research, 2018)
Objective: The present study was done to monitor the progress of abdominal wound healing after experimental laparotomy in ewes using Doppler ultrasonography. Materials and methods: Laparotomy was performed in seven apparently healthy indigenous ewes for collection and transfer of embryos. Wound morphology was studied in terms of width of sutured area of internal wound (ventral raphae) and swelling of suture areas, width and contraction rate of external wound. Internal wound healing process was monitor at two days interval by real time B-mode ultrasonography using transabdominal (13 MHz frequency) transducer. The echoes focus or zone of best resolution was adjusted to the point of interest on the screen. Results: The average widths of raphae wounds declined from 7.7±0.18 mm on day 0 to 0.9±0.34 mm on day 20 and were completely healed on day 22 in all ewes. The average widths of skin wound decreased to 0.36±0.14 mm on day 26 from 8.6±0.33 mm on day 0. Conclusion: It was observed that internal wound healed rapidly than external wound. http://doi.org/10.5455/javar.2017.d221